IoT based smart helmet for mining industry application - Eldemerdash, T. (Science and Engineering Research Support Society, 2020)
IoT has been recently expanded across the different application which brought a huge attention to its construction. In the mining field, where a noisy industrial environment can take place in. The main objective of this research is to design and develop a smart helmet system for mining industry application. Where the provided system will keep on monitoring the hazardous events such as temperature, humidity, gas, removal helmet of the miner and obstacle damage to the helmet. The finalized design was built and enhanced with real environmental testing took place in GuaTempurung cave located at Gopeng, Malaysia. The power of the designed helmet system circuit was evaluated with respect to a previous work. The programming and troubleshooting were conducted on mainly two sections, helmet section and control room section. Based on the on the preliminary calculation the outcome results were obtained. Â© 2019 SERSC.